UM ESTUDO ACERCA DA TERAPÊUTICA ANTINEOPLÁSICA - Lauter, Dagmar S.; Oliveira, Daiane d.; Rosanelli, Cleci S. P.; Loro, Marli M.; Kolankiewicz, Adriane C. B.; Gomes, Joseila S. (Salão do Conhecimento, 2013)
Resumo